Auditee Satisfaction impact on Compliance and Corporate image concerning Malaysian SMEs (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This research aims to analyze the possible effects of auditee satisfaction on compliance audit and corporate image in receiving audit services in Malaysia. Raw data were collected via structured questionnaires through email communication. The collected data were analyzed first using descriptive statistics, then followed by correlation analysis to establish the relationship effects of auditee satisfaction as an independent variable on compliance audit and corporate image, both as dependent variables. Lastly, a regression analysis was borne on the model to test the hypotheses. The study found that auditee satisfaction has a significant relationship with compliance and corporate image. This deemed essential to manage SME firms and audit firms alongside academics who may want to further pursue the subject matter. Many SMEs have embraced audits, and according to previous studies, expenditures on audits have substantially increased. Therefore, it is necessary to supervise the spending amount of audit fees to ensure value for money. The research findings are also imperative to scholars, academics, scientists, and researchers by adding to the body of current knowledge on internal audit and risk management. Nonetheless, its sample size limits the study. Therefore, the results do not represent the whole business organization because it is only limited to retails and wholesale of SMES firm in Malaysia.